Transcriptome analysis provides novel insights into the soil amendments induced response in continuously cropped Codonopsis tangshen - Zhou, Wuxian; Jiang, Xiaogang; Tan, Xuhui; Li, Darong; Wang, Hua; You, Jinwen; Li, Xiaoling; Zhang, Meide (Frontiers in Plant Science, 2022)
Codonopsis tangshen Oliv (C. tangshen) is an important Chinese traditional medicinal plant with various health benefits. However, the growth of C. tangshen are seriously affected by continuous cropping, which led to the decrease of the yield and quality. A field experiment was conducted to learn the effects of soil amendments on the growth of C. tangshen under continuous cropping condition, and the biological events which occurred at molecular level were investigated. The results indicated that the content of chlorophyll a (Chl a), chlorophyll b (Chl b), and carotenoid (Car) was significantly higher in SCPM (silicon-calcium-potassium-magnesium fertilizer), SCPMA (SCPM combined with azoxystrobin) and SCPMAOM (SCPM combined with azoxystrobin and organic manure) treatments. Moreover, the yield and the levels of alkaloid, polysaccharide, flavone and total protein in the treatments of SCPM, SCPMA and SCPMAOM were significantly higher than those in the control, and these indexes were all highest in the SCPMAOM treatment. RNA-sequencing (RNA-Seq) is an economical and efficient method to obtain genetic information for species with or without available genome data. In this study, RNA-Seq was performed to understand how continuously cropped C. tangshen responded to the soil amendments at the transcriptome level. The number of differentially expressed genes (DEGs) were as follows: CK vs SCPM (719 up- and 1456 down-), CK vs SCPMA (1302 up- and 1748 down-), CK vs SCPMAOM (1274 up- and 1678 down-). The soil amendments affected the growth of C. tangshen mainly by regulating the genes involved in pathways of ‘photosynthesis’, ‘plant hormone signal transduction’, ‘biosynthesis of unsaturated fatty acids’, ‘phenylpropanoid biosynthesis’ and ‘starch and sucrose metabolism’, etc. qRT-PCR was performed to validate the expressions of ten target genes such as CP26, PsaF, and POX, etc, which verified the reliability of RNA-Seq results. Overall, this study revealed the roles and underlying mechanisms of the soil amendments in regulating the growth of continuously cropped C. tangshen at transcriptome level. These findings are beneficial for improving the continuous cropping tolerance and may be valuable for future genetic improvement of C. tangshen.